Effect of Humic Acid Addition on Buffering Capacity and Nutrient Storage Capacity of Soilless Substrates - Xu, Jingcheng; Mohamed, Esraa; Li, Qiang; Lu, Tao; Yu, Hongjun; Jiang, Weijie (Frontiers in Plant Science, 2021)
Excessive application of fertilizers has become a major issue in croplands of intensive agricultural systems in China, resulting in severe non-point source pollution; thus, the reduction in the use of chemical fertilizers has received significant attention. Improving the nutrient storage capacity of soils or substrates is an effective approach for solving this problem. Humic acids (HA) are excellent soil conditioners. Thus, in the present study, their ability to improve the physico-chemical properties of three substrates with different textures was evaluated. HA treatments included 1% HA root application in three different types of substrates, including pure sand, pure cocopeat, and a mixture of sand:cocopeat (1:1, v/v) and their relative controls. We examined the morphological parameters of cucumber seedlings, as well as pH buffering capacity (pHBC), total organic carbon (TOC), organic matter (OM), cation exchange capacity (CEC), and nutrient storage capacity of the three substrates. The results showed that HA application improved the morphological parameters of cucumber seedlings (plant height, stem diameter, and biomass) in pure cocopeat and cocopeat-sand mixture treatments. On the contrary, HA addition had harmful effects on the cucumber seedlings cultivated in sand due to the low pHBC of sand. The seedlings cultivated in pure cocopeat showed the best morphological parameter performances among the seedlings grown in the three substrates. Furthermore, pHBC, TOC, OM, and CEC were enhanced by HA application. Incorporation of HA improved ammonium (NH4+) and potassium (K+) storage capacity while decreasing phosphorus (P) storage. Pure cocopeat had the highest pHBC, TOC, OM, CEC, and nutrient storage capacity among the three substrates. In conclusion, mixing 1% HA into substrates promoted cucumber growth, improved substrate properties, and enhanced fertilizer use efficiency. Pure cocopeat is a suitable substrate for cucumber cultivation, and mixing cocopeat with sand amends the substrate properties and consequently improves plant growth.